RELEVANSI IMPLEMENTASI PSAK 109 TERHADAP GOOD CORPORATE GOVERNANCE PADA LEMBAGA ZIS: KAJIAN STUDI PUSTAKA - Saifudin, Ahmad; Anik, Anik (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2025)
Zakat, Infaq, and Sadaqah (ZIS) management institutions play a crucial role in promoting social welfare equality in Indonesia, thus requiring accountable and transparent reporting. PSAK 109, issued by the Indonesian Institute of Accountants (IAI), serves as the accounting standard for the recognition, measurement, presentation, and disclosure of ZIS funds in accordance with Sharia principles. This study examines the relevance of PSAK 109 as a strategic instrument for ZIS governance based on the five pillars of Good Corporate Governance (GCG). The research employs a literature review and content analysis of academic literature, regulations, and institutional reports. The results indicate that PSAK 109 supports GCG by enhancing transparency, accountability, responsibility, independence, and equitable distribution of funds. Structured implementation of PSAK 109 has been shown to strengthen muzakki trust, expand fund collection, and improve internal controls—for instance, a study of BAZNAS West Java reported a 72.1% contribution to good zakat governance. PSAK 109 is not only a technical guideline but also a strategy for establishing professional and sustainable ZIS governance. Future research is recommended to compare implementation across regions, develop GCG evaluation models based on maqashid sharia, and explore the integration of reporting technology.